Patient-Reported Outcomes After Structural Autograft for Large or Cystic Talar Dome Osteochondral Lesions. (May 2020) - Kim, Todd; Haskell, Andrew
Background: While smaller talar dome osteochondral lesions (OCLs) are successfully treated with bone marrow stimulation techniques, the optimal treatment for large or cystic OCLs remains controversial. This study tested the hypothesis that transferring structural autograft bone from the distal tibia to the talus for large or cystic OCLs improves pain and function. Methods: Thirty-two patients with large or cystic OCLs underwent structural bone grafting from the ipsilateral distal tibia to the talar dome. Patients were assessed with subjective patient-centered tools and objective clinical outcomes. Average age was 48.6 ± 14.9 years, and average follow-up was 19.5 ± 13.3 months. Average lesion area was 86.2 ± 23.5 mm 2, and average depth was 8.4 ± 3.0mm. Results: At final follow-up, improvement compared to preoperative scores was seen in American Orthopaedic Foot & Ankle Society (65.4 ± 21.2 to 86.9 ± 15.0, P < .05), Foot Function Index (48.9 ± 20.8 to 21.1 ± 18.9, P < .05), visual analog scale for pain (4.7 ± 3.0 to 1.4 ± 1.5, P < .05), and Patient-Reported Outcomes Measurement Information System (PROMIS) Physical Function (40.4 ± 5.4 to 45.5 ± 7.4, P < .05) scores. There was no improvement in PROMIS pain interference (54.7 ± 18.1 to 52.4 ± 7.3, P > .05). Satisfaction with surgery was 8.4 ± 1.3/10, and 96% of patients would have the procedure again. Ninety-four percent of patients returned to work and/or play. One patient had a deep vein thrombosis 6 weeks postoperatively, and 1 patient underwent ankle fusion at 18 months postoperatively. Conclusion: This study demonstrates that structural bone graft harvested from the distal tibia transferred to the talus was a safe and effective treatment for large and cystic OCLs. Outcomes compare favorably to other described techniques for treatment of these injuries. Level of Evidence: Level IV, case series.